Investigating the Nature of Orientalism from a Philosophical-Historical Point of View Based on the Relationship between Subject and Object - Ghorban Elmi; Alireza Nahri (Comparative Theology)
This article examined the emergence of the human subject as the central focus of modern thought, tracing its origins from the Renaissance period through the Enlightenment. Using a descriptive-analytical approach, it explored the philosophical foundations of Orientalism and the underlying principles it shared with modernity. The analysis revealed that the rise of the human subject in the modern era was accompanied by a shift in perspective. Pre-Renaissance religion and culture were approached with an "objective understanding" by the modern subject. This same subject then went on to apply an "Orientalist understanding" when engaging with non-Western cultures and belief systems. The nature of Orientalism could be located in this novel relationship between the subject and the object of knowledge. The "objective understanding" embodied the Kantian epistemology, wherein the subject, relying solely on its own prior information and independent of any external or divine referent, did not recognize anything beyond itself. By subsuming objects within its own framework, the subject imposed its own understanding upon them. This process of objectification and imposition characterized the Orientalist worldview, which emerged as a core feature of modern thought. The article thus elucidated the deep historical linkages between the ascendance of the autonomous human subject, the principles of modernity, and the rise of Orientalist modes of understanding non-Western cultures and belief systems. Keywords: Orientalism, Principles of Modernity, Subject, Object, Religion. IntroductionThis article investigated the nature of Orientalism as the outward-facing manifestation of modernity's engagement with non-Western religions and cultures. The essence of Orientalism is rooted in the particular relationship it establishes between the subject and the object of knowledge. In the current post-modern historical context, understanding the fundamental nature of Orientalism is a crucial first step towards moving beyond its limiting paradigm of objective research and inquiry. To this end, the article traced the emergence of the human subject as the central focus of modern philosophical thought, dating back to the Renaissance period. Despite the significance of this topic, there was a dearth of independent research specifically devoted to elucidating the essential character of Orientalism. This analysis aimed to fill that gap, providing a nuanced examination of how the rise of the autonomous modern subject gave rise to the Orientalist mode of engaging with non-Western civilizations and belief systems. By excavating the philosophical foundations underpinning Orientalism, the article lay the groundwork for a more critical and self-aware approach to the study of cultures and religions outside the Western ambit. This foundational understanding was a necessary precursor to transcending the limitations of the Orientalist epistemic framework. Materials & MethodsThis article employed a descriptive-analytical-critical approach to examine and elucidate the philosophical and historical foundations of Orientalism. Particular emphasis was placed on the relationship between the subject and the object of knowledge, as well as Kant's critical perspective on this dynamic. Research FindingsOne of the most fundamental philosophical problems - the relationship between the mind and the object - underwent a profound transformation in the Renaissance and Enlightenment periods. This shift in the subject-object dynamic gave rise to a new understanding of truth, the world, and all forms of existence.The most significant change in the subject-object relationship was encapsulated in Kant's critical philosophy, which he described as a "Copernican revolution" in philosophy. This issue lay at the very heart of modern culture. Modernity's engagement with the religious and cultural pasts of Europe and non-European civilizations was centered around this reconfigured subject-object dynamic.In Kantian epistemology, the understanding of the subject does not involve a direct apprehension of objects. Rather, the subject imposes its own a priori information and categories upon the objects it seeks to know. This type of knowledge, by its very nature, entails the domination and possession of those objects. In other words, it exemplifies the logic of "objective understanding." It was through this Kantian framework of the subject-object relationship that the essential character of Orientalism could be grasped. The Orientalist worldview arose directly from the epistemic posture formulated in Kant's critical philosophy. Discussion of Results & ConclusionOrientalism constructs and identifies cultures and religions as "the Orient" - ascribing an essential, reified quality to them. Through its scholarly endeavors, Orientalism effectively reshaped and repackaged the religions, cultures, and literatures of non-Western societies into a modernized, ostensibly "objective" form. Beyond simply collecting historical information about these non-Western civilizations, Orientalists also imparted upon them a particular mode of thinking and perceiving religion, the world, history, and culture. They encouraged non-Westerners to view their own pasts through a Western lens. In the context of this supposedly "objective" research, the religious, cultural, and historical truths of non-Western societies became subsumed under the Orientalist scholar's own frameworks of understanding. The essential nature and spiritual truths of these religions and cultures were effectively obscured and occluded. This dynamic was rooted in the philosophical principle encapsulated in Kant's critical philosophy - that the understanding of the subject could never directly apprehend objects as they truly were. Rather, the subject necessarily imposed its own a priori forms of cognition upon the object, effectively dissolving the object into the subject's own prior knowledge and conceptual categories. It was this Kantian epistemology that underpinned the Orientalist mode of engagement with non-Western religions and cultures. Orientalism, at its core, reflected the subject's inability to know the object outside of the forms and frameworks it projected upon that object. The truth and essence of the non-Western "other" became filtered through and distorted by the Orientalist subject's own preconceptions and intellectual dispositions.